CALCULATION OF A GLARE STOP FOR TWO-MIRROR EXTRA-FOCAL OBJECTIVE - L. F. Zambrano; N. K. Artyukhina; L. V. Peroza (Приборы и методы измерений)
Recently, efforts to improve optical characteristics in canonical mirror systems, including aspherical surfaces and corrective aberration capabilities. At the same time, much attention is paid to the development of new optical schemes of two-mirror objectives. Development measures to protect the image plane from stray light and harmful flows with minimal vignetting and screening is one of the most perspective ways for improving the image quality objectives. The only method to eliminate or even reduce these non-constructive rays is to set glare stops. The aim of the work was an improving method for constructing a glare stop to protect the image plane and the creation of a calculation algorithm of glare stop for protecting the image plane based on two-mirror extra-focal objectives.The study was conducted in two stages. In the course of the first stage, the positions of screening and intermediate image plane were obtained, as well as the central screening coefficient. At the second stage, an arrangement for the position of glare stop is proposed using the algorithm calculation. Thus, mathematical expressions were achieved by geometric constructions. The relation of the screening coefficient with the distance between the surfaces of the mirrors and the height of the paraxial rays is established. А representation of vignetting diagram for two-mirror extra-focal objective with D/f´ = 1 : 1,3 and 2ω = 4° was realized. The Q estimation of vignetting of inclined light beams is k= 0,56.